Research on Antenna Propagation Loss Model in Rail Transit Tunnel based on Multi-dimensional Scenario Analysis - ZHAO Yifan; ZOU Jinbai; ZHAO Zhenglian; XU Zhipeng; ZHOU Qing (Chengshi guidao jiaotong yanjiu)
［Objective］ As tunnel is one of the typical environments for rail transit wireless communication, the accurate prediction of radio wave signal strength in tunnels has always attracted wide attention and study. With the increasing frequency of wireless communication, the application of wireless radiation in tunnels using antenna is becoming more and more widespread. To solve the problems such as the complexity of the existing radio wave propagation loss model in tunnels and the challenges for the model′s validation and application, the on-site measurement results of previous researchers are sorted out, and the characteristics of radio wave signal propagation loss radiated by antenna in the scenario of vacant rail transit tunnels are studied. ［Method］ The models and parameters used in the related research on tunnel antenna propagation loss are analyzed. By segmentally analyzing the frequency and the distances of signal propagation in the near and far fields, the measured data containing multi-dimensional parameters (frequency, signal propagation distance, and tunnel cross-sectional area) are fitted and corrected with the matrix-based least squares method. A radio wave signal propagation loss model of antenna radiation in the scenario of vacant rail transit tunnels is proposed. ［Result & Conclusion］ The verification results show that the above model can predict the propagation loss within the error range and has certain application value in that it is helpful to tunnel wireless communication system design, and can provide reference for the design of antenna coverage schemes of communication systems in rail transit tunnels.